2021
DOI: 10.24815/jdab.v8i2.21335
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of XBRL Adoption on Financial Reporting Timeliness: Evidence from Indonesian Banking Industry

Abstract: This study examines the impact of eXtensible Business Reporting Language (XBRL) adoption on financial reporting timeliness. The population are banking companies listed on the Indonesian Stock Exchange (IDX) between 2015 and 2019. The samples are 38 Indonesian banks or 190 bank-year observations. Using logistic regression this study demonstrates the XBRL adoption positively affects financial reporting timeliness.  The findings confirm that XBRL adoption benefit banks as it stimulates automation process, improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 30 publications
1
7
0
1
Order By: Relevance
“…Proceedings of the 5 th European International Conference on Industrial Engineering and Operations Management Rome, Italy, July 26-28, 2022© IEOM Society InternationalThis result is in line with researches fromLestari et al (2021) andAksoy et al (2021) which prove that XBRL format in financial reporting increase the timely submission of financial reports.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…Proceedings of the 5 th European International Conference on Industrial Engineering and Operations Management Rome, Italy, July 26-28, 2022© IEOM Society InternationalThis result is in line with researches fromLestari et al (2021) andAksoy et al (2021) which prove that XBRL format in financial reporting increase the timely submission of financial reports.…”
supporting
confidence: 78%
“…Prior researches from Lestari et al (2021) and Aksoy et al (2021) claim that XBRL format in financial reporting increase the timely submission of financial reports. Nevertheless, another research from Rao and Guo (2021) found that XBRL format in financial reporting not improve the timely submission of financial reports.…”
Section: Extensible Business Reporting Language (Xbrl)mentioning
confidence: 99%
“…XBRL adoption has several advantages over traditional reporting formats such as PDF or HTML; reduced information asymmetry (Tzu-Yi, Fengyi, Shih-Hsuan, & Kwo-Liang, 2016; Kim, Kim, & Lim, 2019), enhances the reliability and accuracy of financial information (Alsharayri & Al-Arabiat, 2021;Lestari, Putri, & Devi, 2021), present both financial and non-financial information under a single financial report (Ashoka & Abhishek, 2018), and improve consistency, relevance, reliability, and transparency in financial reporting (Wang, 2015;Ashoka & Abhishek, 2018;Kim, Kim, & Lim, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Early empirical evidence has documented mixed results regarding the impact of XBRL adoption on the stock market. Some studies suggest that mandatory XBRL broadens the investor base or ownership (Kim, Kim, & Lim, 2019;Lestari, Putri, & Devi, 2021), boosts investor confidence and revitalizes the stock market, and ensures access to efficient and competitive capital market (Benbouali & Berberi, 2018), improves forecast quality (Burd, 2022), and reduces cost of equity (Tohang & Lusiana, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation